Magnetohydrodynamic flow and heat transfer of ferrofluid in a channel with non-symmetric cavities - Hussain, Shafqat; Öztop, Hakan Fehmi; Qureshi, Muhammad Amer; Abu-Hamdeh, Nidal (Springer, 2020)
This paper explores the heat transfer characteristics and fluid flow of ferrofluid in a channel having non-symmetric cavities under the applied magnetic field. Bottom surface of the cavity is uniformly heated, whereas ceiling of the top cavity is cooled isothermally. The dimensionless governing equations for various physical parameters are computed via a higherorder and stable Galerkin-based finite element technique. Effective governing parameters are nanoparticle volume fraction; (0 <= phi <= 0.15), aspect ratio of the cavities; (0.2 <= h/H <= 1.0), Richardson number; (0.01 <= Ri <= 10), Hartmann number; (0 <= Ha <= 100); and Reynolds number; (1 <= Re <= 200). It is found that the most important parameter is the geometry such that there is an optimal value to maximize the heat transfer. Moreover, it is also noticed that the heat transfer is reduced with strong magnetic field, namely Hartmann number.
Keywords: Mixed convection; Ferrofluid; Magnetohydrodynamics; Galerkin finite element method; Channel with non-symmetric cavities